Penerapan Metode Pembelajaran Mandiri Di Masa Pandemi Covid 19 Pada Pembelajaran Ips - Elliya; Supian, Muhamad (Universitas Muhammadiyah Yogyakarta, 2022)
Pandemic Covid which is still increasing, has an impact on the world of education. so this is one of the considerations for the Indonesian government to adopt policies so that the health and safety of students, educators, education staff, families and society in general are always protected. With the outbreak of the Covid 19 case, the learning method which generally takes place face to face (offline) has changed its direction to online. With learning that is done online, it indirectly makes students to do learning independently. The purpose of this study is to describe in general the application of the independent learning method in PKBM Harati Sampit, which is a non-formal institution located on Jl. Scouts KM 1.5 Sampit and has an equality program packages A, B and C. As a forum to serve and help the community to obtain an equal and quality education. Have a flexible learning system both face to face, tutorial or independently. The research method used is a qualitative approach with a descriptive research design. Data collection techniques are by way of observation, interviews and documentation related to the learning methods used. The results of the study show that the application of the use of independent learning methods during the covid 19 pandemic in social studies learning at the Harati Sampit Community Learning Activity Center (PKBM) for distance learning is still quite effective even though there are many obstacles faced by learning residents, including limited mobile phones and cellular networks. However, online learning is an appropriate learning program to use and is the best solution during the current pandemic to break the chain of transmission of COVID-19.